A fatal case of primary cardiac chondrosarcoma presenting with amaurosis fugax. (5th October 2015) - Sundbøll, Jens; Hansson, Nils Henrik Stubkjær; Baerentzen, Steen; Pareek, Manan
Abstract : A 64-year-old previously healthy woman consulted her general practitioner because of recurrent episodes of right-sided monocular transient visual loss (ie, amaurosis fugax). At first, these symptoms were followed over time, but as the attacks worsened, and were accompanied by dizziness and general discomfort, the patient was admitted to the department of neurology for further investigations. CT of the brain was normal; however, during admission, the patient developed rapid atrial fibrillation and was transferred to the department of cardiology. Transthoracic echocardiography revealed a massive tumour on the atrial side of the anterior mitral valve leaflet, partly obstructing the mitral valve inflow. The tumour was excised and a biological prosthetic mitral valve inserted. The tumour was histologically determined to be a highly malignant dedifferentiated chondrosarcoma. After 6 months, the tumour relapsed and expanded aggressively to completely obstruct the mitral valve inflow, ultimately leading to cardiac arrest and death.